2015
DOI: 10.1111/cobi.12475
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic understanding of human–wildlife conflict through a novel application of dynamic occupancy models

Abstract: Crop and livestock depredation by wildlife is a primary driver of human-wildlife conflict, a problem that threatens the coexistence of people and wildlife globally. Understanding mechanisms that underlie depredation patterns holds the key to mitigating conflicts across time and space. However, most studies do not consider imperfect detection and reporting of conflicts, which may lead to incorrect inference regarding its spatiotemporal drivers. We applied dynamic occupancy models to elephant crop depredation da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 29 publications
3
72
2
Order By: Relevance
“…Indeed, collared elephants spent nearly 30% of their time in croplands between September and November. This contrasts with the results of some previous studies that have reported peaks in crop raiding by elephants associated with higher rainfall (e.g., Goswami, Medhi, Nichols, & Oli, ; Osborn, ; Sukumar, ). This discrepancy likely is at least partially related to ease of access to irrigation water in our study area.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, collared elephants spent nearly 30% of their time in croplands between September and November. This contrasts with the results of some previous studies that have reported peaks in crop raiding by elephants associated with higher rainfall (e.g., Goswami, Medhi, Nichols, & Oli, ; Osborn, ; Sukumar, ). This discrepancy likely is at least partially related to ease of access to irrigation water in our study area.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we also sought to (4) evaluate the efficacy of ranger patrols in reducing poaching‐related threats in NNP. We used dynamic occupancy models to analyse the data (MacKenzie et al., , ) because they provide a rigorous statistical framework for estimating relevant parameters while also accounting for imperfect detection of threats by rangers (Goswami et al., ; Linkie et al., ; MacKenzie et al., ; Sharma, Wright, Joseph, & Desai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical models have been extensively used in the field of applied conservation research to parse processes of interest (here, attitudes of respondents) from observational processes (in our case, misreporting) (Williams et al 2002;Royle & Dorazio 2008;Lachish et al 2012;Goswami et al 2015). These models have been used previously on data obtained from questionnaire surveys as well, accounting simultaneously for probabilities of falsepositive and false-negative reporting (e.g., Pillay et al 2014).…”
Section: Discussionmentioning
confidence: 99%